Precious metal-SiO2 (at) CuS hydrogen-sensitive color-changing material as well as preparation method and application thereof
Through the preparation method of precious metal-SiO2@CuS hydrogen-sensitive discoloration material, the existing hydrogen detection methods have not changed color significantly and complicated processes have been solved, and the efficient, environmentally friendly and industrial applicability of hydrogen detection has been achieved.
Patent Information
- Application Number
- CN202411577628.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing hydrogen detection methods have problems such as lack of color discoloration, difficulty in distinguishing naked eyes, and lack of color discoloration, or problems such as complex processes, environmental pollution, and insufficient industrialization capabilities, making it difficult to meet the growing demand for hydrogen detection.
The noble metal-SiO2@CuS hydrogen-sensitive discoloration material is used. The preparation method includes reacting the silicon-based material with copper chloride in a mixed solution of oleamine and oleic acid, and then reacting with sulfur powder in oleic acid to form SiO2@CuS nanoparticles, and adding the noble metal-based material to ethylene glycol, and forming the noble metal-SiO2@CuS hydrogen-sensitive discoloration material through high temperature reaction.
The hydrogen-sensitive discoloration material does not fade under normal storage, and changes color significantly after contacting hydrogen. It has a short response time. It has excellent hydrogen discoloration sensitivity and indication effect. It can restore the initial color in the air. It is suitable for recycling. The preparation method is simple and efficient, with low cost, and is suitable for industrial applications.
Smart Images

Figure CN119614178A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic materials, and in particular relates to a noble metal-SiO2@CuS hydrogen-sensitive color-changing material and a preparation method and application thereof. Background Art
[0002] Hydrogen is an efficient, clean, and renewable energy source. However, hydrogen is very easy to leak during production, use, storage, and transportation. It is colorless and odorless, and is difficult to detect. In addition, hydrogen has strong permeability and is prone to explosion. Therefore, hydrogen leakage detection is a crucial link in ensuring safety.
[0003] Hydrogen-sensitive color-changing materials are materials that change color when exposed to hydrogen. The color-changing principle is usually based on the chemical reaction or physical change that occurs when the material comes into contact with hydrogen molecules. These changes may involve changes in electronic structure, lattice changes, or other changes in intermolecular forces, which in turn lead to color changes. For example, tungsten trioxide (WO3) is an important gas-sensitive material that has good sensitivity to hydrogen after being doped with precious metals Pd and Pt. When the WO3 film is exposed to hydrogen, a reduction reaction occurs on its surface, resulting in W 6+ ions are reduced to W 5+ or W 4+ ions, thereby changing the optical properties of the material and producing a color change.
[0004] Hydrogen-sensitive color-changing materials have broad application prospects in hydrogen leak detection. They can intuitively display the presence of hydrogen through color changes. This material can be used to monitor hydrogen leaks in real time and improve safety. For example, in hydrogen refueling stations, hydrogen fuel cell vehicles, chemical plants, hydrogen production industries and other places, hydrogen-sensitive color-changing materials can be used for leak detection in key parts such as pipelines and valves.
[0005] In recent years, researchers have improved the sensitivity and stability of materials by optimizing the material preparation process, doping and modification, and other methods. For example, advanced preparation techniques such as sol-gel method and magnetron sputtering method can be used to prepare hydrogen-sensitive films with high specific surface area and porous structure, thereby improving the hydrogen adsorption capacity and response speed of the material. In addition, the hydrogen-sensitive performance of the material can be further improved by doping with active substances such as precious metals and transition metal oxides.
[0006] Patent CN111662650A involves mixing a binder (including polysiloxane, reinforcing additives, crosslinking agents and catalysts) with a color-changing material (such as metal oxides and nano-metal particles) in a kneader, and then forming a ribbon-shaped sheet through an extruder to finally make a tape. The tape can show three color transitions: light yellow to blue, dark brown to light brown, and light gray to blue. However, in this patent, the color change of the material is relatively monotonous, and the difference between the latter two groups of colors is subtle, which is challenging to identify with the naked eye.
[0007] Patent CN112592708A uses WO3 and metal elements (Fe, Pt, Y) as active ingredients and loads them on a variety of carriers such as Al2O3, TiO2, SiO2, molecular sieves, kaolin, bentonite and diatomaceous earth. This process covers a series of cumbersome steps such as impregnation, drying, reaction, roasting, remixing, standing, solid-liquid separation, secondary drying and re-roasting. Therefore, the process involved in this patent is not only complicated, but also has many steps, is time-consuming, and inefficient, making it difficult to achieve large-scale production and application.
[0008] In summary, the existing hydrogen detection methods have problems such as unclear color change, difficult to distinguish with the naked eye, and limited color change, or have complex procedures, environmental pollution, and insufficient industrialization capabilities, which make it difficult to meet the growing demand for hydrogen detection. Summary of the invention
[0009] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a noble metal-SiO2@CuS hydrogen-sensitive color-changing material.
[0010] Another object of the present invention is to provide a method for preparing the above-mentioned noble metal-SiO2@CuS hydrogen-sensitive color-changing material.
[0011] Another object of the present invention is to provide an application of the above-mentioned noble metal-SiO2@CuS hydrogen-sensitive color-changing material in detecting hydrogen.
[0012] The present invention is achieved by providing a method for preparing a noble metal-SiO2@CuS hydrogen-sensitive color-changing material, the method comprising the following steps: (1) dispersing 0.5-2 mmol of silicon-based material in 5-20 mL of a mixed solution of oleylamine and oleic acid, adding 0.5-4 mmol of copper chloride, stirring and reacting at 80-100° C. for 5-7 hours to obtain a reaction solution; (2) dispersing 0.5-4 mmol sulfur powder into 5-10 mL oleic acid and adding the mixture into 10-20 mL of the reaction solution, stirring the mixture at 80-100° C. for 5-7 hours, washing the reaction product by centrifugation, and collecting the resulting precipitate as SiO2@CuS nanoparticles; (3) adding the SiO2@CuS nanoparticles to 50-200 mL of ethylene glycol, wherein the concentration of the SiO2@CuS nanoparticles is 5-10 g / mL, stirring and mixing, and dropwise adding 5-10 mL of an ethylene glycol solution containing 5-15 mg of a noble metal-based material, or dropwise adding 10-20 mL of a methanol solution containing 5-15 mg of a noble metal-based material and 10-50 mg of polyvinyl pyrrolidone, stirring and dispersing evenly to obtain a dispersion; wherein the noble metal-based material is palladium (II) acetylacetonate or a mixed material consisting of palladium (II) acetylacetonate and chloroplatinic acid; (4) reacting the dispersion at 100-180° C. for 2-12 h, centrifuging the reaction solution, and collecting the resulting precipitate as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material.
[0013] Preferably, in step (1), the silicon-based material is selected from any one of mesoporous silica, silica particles, and thin layer chromatography silica gel.
[0014] Preferably, in step (1), the volume ratio of oleylamine to oleic acid in the mixed solution is 1-2:1-2.
[0015] Preferably, in step (2), the centrifugal washing is performed by using a washing solution and centrifuging at a speed of 8000 rpm for several times, wherein the washing solution is composed of 1 part by volume of cyclohexane and 2 to 5 parts by volume of anhydrous ethanol.
[0016] Preferably, in step (3), the dropping rate is 5-10 mL / min.
[0017] Preferably, in step (3), in the mixed material, the mass ratio of palladium (II) acetylacetonate to chloroplatinic acid is 1-2:1-2.
[0018] Preferably, in step (4), the reaction solution is centrifuged to retain the upper layer solution, and the precious metal-based material in the upper layer solution is reused.
[0019] The invention further discloses a noble metal-SiO2@CuS hydrogen-sensitive color-changing material prepared by the method.
[0020] The present invention further discloses the application of the noble metal-SiO2@CuS hydrogen-sensitive color-changing material in hydrogen detection.
[0021] The present invention overcomes the deficiencies of the prior art and provides a noble metal-SiO2@CuS hydrogen-sensitive color-changing material and a preparation method and application thereof. The present invention disperses a silicon-based material in a mixed solution of oleylamine and oleic acid, adds copper chloride, and stirs and reacts at 80-100°C for 5-7 hours to obtain a reaction solution; then disperses sulfur powder in oleic acid and adds it to the reaction solution, stirs and reacts at 80-100°C for 5-7 hours, centrifuges and washes the reaction product, and collects the resulting precipitate as SiO2@CuS nanoparticles; finally, adds the SiO2@CuS nanoparticles to ethylene glycol, stirs and mixes, drops an ethylene glycol solution containing a noble metal-based material, or drops a methanol solution containing a noble metal-based material and polyvinyl pyrrolidone, stirs and disperses evenly, reacts at 100-180°C for 2-12 hours, centrifuges the reaction solution, and collects the resulting precipitate as a noble metal-SiO2@CuS hydrogen-sensitive color-changing material.
[0022] In the present invention, the hydrogen-sensitive color-changing material is mainly composed of a multi-level layered structure formed by an inner base layer (SiO2), a middle color-changing layer (CuS), and an outermost catalyst layer (precious metal). In this structure, the SiO2 of the base layer increases the specific surface area of the hydrogen-sensitive color-changing material, and its unique porous characteristics have a positive effect on the adsorption of hydrogen, which can increase the amount of hydrogen adsorbed by the material, thereby shortening the time of hydrogen-sensitive color change, and also reduce the preparation cost of the material; when the hydrogen-sensitive color-changing material contacts with hydrogen, the hydrogen is first activated by the precious metal of the catalyst layer and converted into active hydrogen atoms, which then react chemically with the color-changing layer. Specifically, the transition metal oxide (CuS) in the color-changing layer is reduced by hydrogen to a metal hydride, thereby causing a change in the color of the color-changing layer, and finally manifesting as a change in the color of the hydrogen-sensitive color-changing material. In addition, when the hydrogen-sensitive color-changing material that has changed color is fully in contact with the air, it can be restored to its initial color state, so the hydrogen-sensitive color-changing material can be recycled.
[0023] Compared with the shortcomings and deficiencies of the prior art, the present invention has the following beneficial effects: (1) The noble metal-SiO2@CuS hydrogen-sensitive color-changing material of the present invention has the characteristics of not fading under normal storage and being environmentally friendly. In addition, the hydrogen-sensitive color-changing material changes color obviously after contacting hydrogen, has a short response time, and has excellent hydrogen color-changing sensitivity and indication effect; (2) The noble metal-SiO2@CuS hydrogen-sensitive color-changing material of the present invention can be restored to its initial color state in the air after being out of contact with hydrogen, and the hydrogen-sensitive color-changing material can be reused; (3) The preparation method of the noble metal-SiO2@CuS hydrogen-sensitive color-changing material of the present invention is simple and efficient, and the heavy metal raw materials can be reused in the subsequent preparation process of the catalytic layer, which greatly reduces the cost of the materials, is environmentally friendly, and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the color change and reduction process of the hydrogen-sensitive color-changing material 1 in the embodiment of the effect of the present invention; wherein, Figure a is the initial color of the hydrogen-sensitive color-changing material 1, Figure b is the color after the hydrogen-sensitive color-changing material 1 reacts completely with hydrogen, and Figure c is the color after the hydrogen-sensitive color-changing material 1 is fully reduced with air; Figure 2 This is the color change and reduction process of the hydrogen-sensitive color-changing material 8 in the embodiment of the effect of the present invention; wherein, Figure a is the initial color of the hydrogen-sensitive color-changing material 8, Figure b is the color of the hydrogen-sensitive color-changing material 8 after complete reaction with hydrogen, and Figure c is the color of the hydrogen-sensitive color-changing material 8 after sufficient reduction with air. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Example 1
[0026] (1) 20 mL of hexadecyltrimethylammonium bromide and 1 mL of triethanolamine were mixed, 10 mL of ethyl silicate was added, and the mixture was reacted at 95°C for 1 hour. The reaction product was added into 100 mL of a saturated methanol solution of sodium chloride (the mass molar concentration of NaCl in methanol at room temperature is 0.238 mol / kg) and stirred to extract the hexadecyltrimethylammonium bromide. The mixture was washed with a washing liquid for 4 times at 8000 rpm for 10 minutes each time to obtain mesoporous silica; wherein the washing liquid was prepared by 1 part by volume of cyclohexane and 2 parts by volume of anhydrous ethanol; 2 mmol of mesoporous silica was dispersed in 5 mL of a mixed solution (composed of oleylamine and oleic acid in a volume ratio of 1:2), 0.5 mmol of copper chloride was added, and the mixture was stirred at 90°C for 6 hours to obtain a reaction solution; (2) 0.5 mmol sulfur powder was dispersed in 10 mL oleic acid and added to 20 mL of the reaction solution of step (1), and the mixture was stirred at 100°C for 5 hours. The reaction product was centrifuged and washed three times at 8000 rpm with a washing solution (prepared with 1 volume part of cyclohexane and 2 volume parts of anhydrous ethanol), each time for 10 minutes, and the resulting precipitate was collected as SiO2@CuS nanoparticles; (3) Add SiO2@CuS nanoparticles to 200 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 10 g / mL), stir to mix, and add 20 mL of methanol solution containing 15 mg of acetylacetonate palladium (II) and 10 mg of polyvinyl pyrrolidone dropwise at a rate of 10 mL / min, stir and disperse evenly to obtain a dispersion; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 100°C for 2 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 1. Example 2
[0027] (1) 0.5 mmol of the mesoporous silica prepared in Example 1 was dispersed in 20 mL of a mixed solution (composed of oleylamine and oleic acid in a volume ratio of 1:1), 4 mmol of copper chloride was added, and the mixture was stirred and reacted at 80° C. for 5 h to obtain a reaction solution; (2) 4 mmol of sulfur powder was dispersed in 5 mL of oleic acid and added to 10 mL of the reaction solution of step (1), and the mixture was stirred at 80°C for 7 hours. The reaction product was washed with a washing solution (composed of 1 volume part of cyclohexane and 2 volume parts of anhydrous ethanol) and centrifuged at 8000 rpm for 3 times, each time for 10 min, and the resulting precipitate was collected as SiO2@CuS nanoparticles; (3) Add SiO2@CuS nanoparticles to 50 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 5 g / mL), stir to mix, and add ethylene glycol solution containing 5 mg of acetylacetonate palladium (II) dropwise at a rate of 5 mL / min, stir and disperse evenly to obtain a dispersion; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 180°C for 12 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 2. Example 3
[0028] This embodiment 3 is basically the same as embodiment 1, except that: (3) Add SiO2@CuS nanoparticles to 100 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 8 g / mL), stir and mix, and add 15 mL of methanol solution containing 10 mg of the mixed material and 30 mg of polyvinyl pyrrolidone dropwise at a rate of 8 mL / min, stir and disperse evenly to obtain a dispersion; wherein the mixed material is composed of acetylacetonate palladium (II) and chloroplatinic acid in a mass ratio of 1:1; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 140°C for 6 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 3. Example 4
[0029] This embodiment 4 is basically the same as embodiment 1, except that: (3) Add SiO2@CuS nanoparticles to 120 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 8 g / mL), stir and mix, and add 15 mL of methanol solution containing 12 mg of the mixed material and 25 mg of polyvinyl pyrrolidone dropwise at a rate of 8 mL / min, stir and disperse evenly to obtain a dispersion; wherein the mixed material is composed of acetylacetonate palladium (II) and chloroplatinic acid in a mass ratio of 1:2; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 160°C for 8 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 4. Example 5
[0030] This embodiment 4 is basically the same as embodiment 1, except that: (3) Add SiO2@CuS nanoparticles to 120 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 8 g / mL), stir and mix, and add 15 mL of methanol solution containing 12 mg of the mixed material and 25 mg of polyvinyl pyrrolidone dropwise at a rate of 8 mL / min, stir and disperse evenly to obtain a dispersion; wherein the mixed material is composed of acetylacetonate palladium (II) and chloroplatinic acid in a mass ratio of 2:1; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 160°C for 8 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 5. Example 6
[0031] (1) 5 mL of ethyl silicate, 100 mL of ethanol, and 5 mL of ammonia solution (the volume ratio of concentrated ammonia to water is 2:1) were mixed in a beaker, and magnetic stirring was performed in a water bath at 25°C to promote the growth of silica particles. The obtained silica particles were washed four times with ethanol and centrifuged at 8000 rpm, each time for 10 min; the washed silica particles were vacuum dried; 1 mmol of silica particles was dispersed in 15 mL of a mixed solution (the mixed solution was composed of oleylamine and oleic acid in a volume ratio of 2:1), 1.5 mmol of copper chloride was added, and the mixture was stirred at 85° C. for 5 h to obtain a reaction solution; (2) 1 mmol of sulfur powder was dispersed in 60 mL of oleic acid and added to 10 mL of the reaction solution of step (1), and the mixture was stirred at 86°C for 5 hours. The reaction product was centrifuged and washed three times at 8000 rpm with a washing solution (prepared with 1 volume part of cyclohexane and 2 volume parts of anhydrous ethanol), each time for 10 minutes, and the resulting precipitate was collected as SiO2@CuS nanoparticles; (3) Add SiO2@CuS nanoparticles to 120 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 7 g / mL), stir to mix, and add 12 mL of methanol solution containing 12 mg of acetylacetonate palladium (II) and 40 mg of polyvinyl pyrrolidone dropwise at a rate of 5 mL / min, stir and disperse evenly to obtain a dispersion; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 130°C for 42 hours. The reaction solution was centrifuged at 10,000 rpm for 3 minutes, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 6. Example 7
[0032] (1) Disperse 2 mmol of thin layer chromatography silica gel (white granular coarse pore silica gel) in 5 mL of a mixed solution (composed of oleylamine and oleic acid in a volume ratio of 2:1), add 0.5% copper chloride, and stir the mixture at 90°C for 6 h to obtain a reaction solution.
[0033] (2) 3 mmol of sulfur powder was dispersed in 8 mL of oleic acid and added to 15 mL of the reaction solution of step (1), and the mixture was stirred at 90°C for 6 hours. The reaction product was centrifuged and washed three times at 8000 rpm with a washing solution (prepared with 1 volume part of cyclohexane and 2 volume parts of anhydrous ethanol), each time for 10 minutes, and the resulting precipitate was collected as SiO2@CuS nanoparticles; (3) Add SiO2@CuS nanoparticles to 100 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 9 g / mL), stir and mix, and add 20 mL of a methanol solution containing 5 mg of acetylacetonate palladium (II) and 50 mg of polyvinyl pyrrolidone dropwise at a rate of 6 mL / min, stir and disperse evenly to obtain a dispersion; (4) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 120°C for 7 h. The reaction solution was centrifuged at 10,000 rpm for 3 min, and the obtained precipitate was collected as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 7. Example 8
[0034] This embodiment 8 is basically the same as embodiment 1, except that after step (4), it further includes the following steps: (5) After centrifuging the reaction solution, collect the upper solution; (6) Add SiO2@CuS nanoparticles to 200 mL of ethylene glycol (the concentration of SiO2@CuS nanoparticles is 10 g / mL), stir to mix, and add 50 mL of the upper layer solution obtained in step (4) dropwise at a rate of 10 mL / min, stir and disperse evenly to obtain a dispersion; (7) The obtained dispersion was transferred into a polytetrafluoroethylene-lined crystallization reactor and reacted at 120°C for 7 h. The reaction solution was centrifuged and the precipitate was collected to obtain the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 8. Effect Example
[0035] 1. After the noble metal-SiO2@CuS hydrogen-sensitive color-changing materials 1~8 prepared in the above Examples 1~8 were exposed to an indoor environment at normal temperature and pressure for 1 month, the observation results showed that the color of the noble metal-SiO2@CuS hydrogen-sensitive color-changing materials 1~8 did not change.
[0036] 2. Color change reaction The noble metal-SiO2@CuS hydrogen-sensitive color-changing material prepared in the above Examples 1 to 8 was subjected to a color-changing reaction. Specifically, the hydrogen-sensitive color-changing material was placed in a 20 mL transparent glass vial, and then pure hydrogen gas was introduced at a flow rate of 300 to 600 mL / min, and the color change of the hydrogen-sensitive material was recorded.
[0037] The results show that the noble metal-SiO2@CuS hydrogen-sensitive color-changing materials prepared in Examples 1 to 8 all change color instantly after contacting hydrogen, and the color changes to the darkest after 10 to 30 seconds. The color-changing effect is very significant and the response speed is fast.
[0038] Among them, the color change reaction process of the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that before the hydrogen is introduced, the color of the hydrogen-sensitive color-changing material 1 in the glass bottle is light yellow ( Figure 1 a), pure hydrogen gas with a flow rate of 300 mL / min is introduced, and the hydrogen-sensitive color-changing material 1 changes color the moment it contacts the pure hydrogen gas. After 10 to 30 seconds, the hydrogen-sensitive color-changing material 1 reacts completely with the hydrogen gas, and the color of the hydrogen-sensitive color-changing material 1 reaches the darkest color, and finally presents a gray-green color ( Figure 1 b), and during the subsequent continuous introduction of hydrogen, the color of the hydrogen-sensitive color-changing material 1 remained essentially unchanged. After the introduction of hydrogen into the vial was stopped and the hydrogen-sensitive color-changing material 1 was allowed to fully contact the air for 10 minutes, the hydrogen-sensitive color-changing material 1 gradually returned to its initial color state ( Figure 1c). The hydrogen-sensitive color-changing material 1 restored to its original color state can be reused for hydrogen detection. After 20 cycles of the experiment, the hydrogen-sensitive color-changing material 1 has no effect on the color change sensitivity of hydrogen.
[0039] The color change reaction process of the noble metal-SiO2@CuS hydrogen-sensitive color-changing material 8, such as Figure 2 As shown. Figure 2 It can be seen that before the hydrogen is introduced, the color of the hydrogen-sensitive color-changing material 8 in the glass bottle is yellow-white ( Figure 2 a) When hydrogen was introduced at a flow rate of 600 mL / min, the hydrogen-sensitive color-changing material 8 changed color instantly, and the color reached the darkest dark green after 10-20 seconds ( Figure 2 b), and during the subsequent continuous introduction of hydrogen, the color of the hydrogen-sensitive color-changing material 8 remained essentially unchanged. After the introduction of hydrogen into the vial was stopped and the hydrogen-sensitive color-changing material 1 was allowed to fully contact the air for 8 minutes, the hydrogen-sensitive color-changing material 8 gradually returned to its initial color state ( Figure 2 c). It can be seen that in Example 8, the reaction solution of step (3) of Example 1 is centrifuged and the upper solution is collected. The heavy metal raw material (Pd) in the upper solution can be reused for preparing the catalytic layer of the hydrogen-sensitive color-changing material, and the color-changing effect and color-changing response ability of the obtained hydrogen-sensitive color-changing material are basically unchanged, which can greatly reduce the material loss cost and is conducive to industrial application.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a noble metal-SiO2@CuS hydrogen-sensitive color-changing material, characterized in that: The method comprises the following steps: (1) dispersing 0.5-2 mmol of silicon-based material in 5-20 mL of a mixed solution of oleylamine and oleic acid, adding 0.5-4 mmol of copper chloride, stirring and reacting at 80-100° C. for 5-7 hours to obtain a reaction solution; (2) dispersing 0.5-4 mmol sulfur powder into 5-10 mL oleic acid and adding the mixture into 10-20 mL of the reaction solution, stirring the mixture at 80-100° C. for 5-7 hours, washing the reaction product by centrifugation, and collecting the resulting precipitate as SiO2@CuS nanoparticles; (3) adding the SiO2@CuS nanoparticles to 50-200 mL of ethylene glycol, wherein the concentration of the SiO2@CuS nanoparticles is 5-10 g / mL, stirring and mixing, and dropwise adding 5-10 mL of an ethylene glycol solution containing 5-15 mg of a noble metal-based material, or dropwise adding 10-20 mL of a methanol solution containing 5-15 mg of a noble metal-based material and 10-50 mg of polyvinyl pyrrolidone, stirring and dispersing evenly to obtain a dispersion; wherein the noble metal-based material is palladium (II) acetylacetonate or a mixed material consisting of palladium (II) acetylacetonate and chloroplatinic acid; (4) reacting the dispersion at 100-180° C. for 2-12 h, centrifuging the reaction solution, and collecting the resulting precipitate as the noble metal-SiO2@CuS hydrogen-sensitive color-changing material.
2. The preparation method according to claim 1, characterized in that In step (1), the silicon-based material is selected from any one of mesoporous silica, silica particles, and thin layer chromatography silica gel.
3. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of oleylamine to oleic acid in the mixed solution is 1-2:1-2.
4. The preparation method according to claim 1, characterized in that: In step (2), the centrifugal washing is performed by using a washing solution and centrifuging at a speed of 8000 rpm for several times, wherein the washing solution is composed of 1 volume part of cyclohexane and 2 to 5 volume parts of anhydrous ethanol.
5. The preparation method according to claim 1, characterized in that: In step (3), the dropping speed is 5-10 mL / min.
6. The preparation method according to claim 1, characterized in that: In step (3), in the mixed material, the mass ratio of palladium (II) acetylacetonate to chloroplatinic acid is 1-2:1-2.
7. The preparation method according to claim 1, characterized in that: In step (4), the reaction solution is centrifuged to retain the upper solution, and the precious metal-based material in the upper solution is reused.
8. The noble metal-SiO2@CuS hydrogen-sensitive color-changing material prepared by the method according to any one of claims 1 to 7.
9. Use of the noble metal-SiO2@CuS hydrogen-sensitive color-changing material according to claim 8 in hydrogen detection.